Meaning behind the Poem: An Analysis of Transitivity of Poems for Students at English Department of Teacher Training and Education Faculty, Mathla’ul Anwar University Banten - Ari Fajria Novari; Rizdki Elang Gumelar (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2022)
The study aims to be analyzed observed meaning in poetry written by English Department at of Teacher Training and Education Faculty, Mathla’ul Anwar University. It applied Halliday Systemic Functional Grammar to identify and analyze the occurrences of processes in the poetry. Gerrot and Wignell (2008:6) explain that the theory of grammar is needed to know the text working. By using the theory, the reader will understand the text clearly. One of the ways to convey meaning is by analyzing the transitivity pattern in the poetry. Transitivity is represented experiential meaning that are meaning about the world experience and what is going on in the clause. The authors applied descriptive analysis method, it was in order to elaborate the appearing process types of transitivity in poems and to describe the percentage of process types. After determining the type of process for each predicator, the percentages were counting and comparing one to another independently in each poem. Further, the choice of processes and patterns lead to the discussion on the purposes and effects. The examination on the transitivity analysis shows that the processes employed to meaning behind the poems using transitivity are material, mental, relational, verbal, and behavioral processes. The processes tell particular significant to the process of meaning. For instance, material processes frequently dominated the meaning of the poems. The other transitivity processes resemble the purpose and effect based on their meanings. Hopefully, this paper might serve an example of how to examine the language patterns in a literary work to further observe the purposes and the effects of the patterns.